Induced Lanthanide Circularly Polarized Luminescence as a Probe of Protein Fibrils - Krupová, Monika (ACS Omega, 2019)
[Image: see text] Protein fibrils are involved in a number of biological processes. Because their structure is very complex and not completely understood, different spectroscopic methods are used to monitor different aspects of fibril structure. We have explored circularly polarized luminescence (CPL) induced in lanthanide compounds to indicate fibril growth and discriminate among fibril types. For hen egg-white lysozyme and polyglutamic acid-specific CPL, spectral patterns were obtained and could be correlated with vibrational circular dichroism (VCD) spectra and thioflavin T fluorescence. The CPL spectra were measured on a Raman optical activity spectrometer, and its various polarization modes are discussed. The experiments indicate that the induced CPL is sensitive to more local aspects of the fibril structure than VCD. For CPL, smaller amounts of the sample are required for the analysis, and thus this method appears to be a good candidate for future spectroscopic characterization of these peptide and protein aggregates.